The Role of Christian Religious Education Teachers in Fostering a Sense of National Unity and Integrity in Junior High School Students in Tanah Sereal-Bogor based on Romans 15:5-7 - Yosrina Nainggolan; Ester Yunita Dewi (Green Philosophy: International Journal of Religious Education and Philosophy, 2024)
The Christian Religious Education teacher plays a strategic role in shaping students' understanding of the importance of living in harmony and peace, despite different backgrounds. However, in practice, not all Christian Religious Education teachers are able to effectively integrate teachings about unity and solidarity. The role of Christian Religious Education teachers in fostering a sense of national unity among Junior High School Tanah Sereal-Bogor students is crucial, especially in the context of Indonesia's diversity. This study aims to examine the strategic role of Christian Religious Education teachers based on guidelines derived from Romans 15:5-7. The research will use a qualitative approach, exploring the role of Christian Religious Education teachers in fostering a sense of national unity among Junior High School Tanah Sereal-Bogor students based on the teachings of Romans 15:5-7. The results show that the implementation of teachings from Romans 15:5-7 in the Christian Religious Education curriculum can have a significant impact on shaping students' characters to have attitudes of national unity and solidarity. Thus, Christian Religious Education teachers act as agents of change who can strengthen the sense of national unity through education based on Christian values.